Konten Youtube Sebagai Referensi Pertimbangan Hakim Dalam Memutuskan Perkara Cerai Talak Pada Pengadilan Agama - Mhd. Khadafi Abdullah; Doni Eka Putra; Yossiramah Sucia (Universitas Sumatera Barat, 2024)
This article is an analysis of the legal considerations of the judges of the Pariaman Religious Court in examining, deciding and adjudicating divorce divorce cases, case number 1129/Pdt.G/2022/PA.Prm. In its considerations, the panel of judges cited YouTube content as a reference for the judge's consideration in deciding the divorce divorce case. YouTube is a social media platform that is commonly used by all people, so the scientific responsibility for the content is still questionable. YouTube content is a source of income for content creators. Namely what is obtained from endorsements and promotions or what is called Active income and what is obtained from video monetization or collaboration between Google Adsense and YouTube by fulfilling certain conditions and criteria which is called passive income. In examining and deciding a case, the panel of judges explores existing legal sources, both formal legal sources and material legal sources. Formal legal sources are legal sources. Formal legal sources are legal sources in terms of their formation. In this formal source of law there are formulations of various rules which are the basis for the binding force of regulations so that they are obeyed by society and law enforcers, while material sources of law are factors that help form law, for example social relations, political power relations, socio-economic situations, prevailing traditions, research results. scientific, international developments, geographical conditions etc.